Influence of early‐life adversity on responses to acute and chronic ethanol in female mice. (16th December 2022) - Okhuarobo, Agbonlahor; Angelo, Maggie; Bolton, Jessica L.; Lopez, Catherine; Igbe, Ighodaro; Baram, Tallie Z.; Contet, Candice
Abstract: Background: Stressful early‐life experiences increase the risk of developing an alcohol use disorder. We previously found that male C57BL/6J mice reared under limited bedding and nesting (LBN) conditions, a model of early‐life adversity, escalate their ethanol intake in limited‐access two‐bottle choice (2BC) sessions faster than control (CTL)‐reared counterparts when exposed to chronic intermittent ethanol (CIE) vapor inhalation. However, the alcohol consumption of female littermates was not affected by LBN or CIE. In the present study, we sought to determine whether this phenotype reflected a general insensitivity of female mice to the influence of early‐life stress on alcohol responses. Methods: In a first experiment, CTL and LBN females with a history of 2BC combined or not with CIE were tested in affective and nociceptive assays during withdrawal. In a second group of CTL and LBN females, we examined ethanol‐induced antinociception, sedation, plasma clearance, and c‐Fos induction. Results: In females withdrawn from chronic 2BC, CIE increased digging, reduced grooming, and increased immobility in the tail suspension test regardless of early‐life history. In contrast, LBN rearing lowered mechanical nociceptive thresholds regardless of CIE exposure. In females acutely treated with ethanol, LBN rearing facilitated antinociception and delayed the onset of sedation without influencing ethanol clearance rate or c‐Fos induction in the paraventricular nucleus of the hypothalamus, paraventricular nucleus of the thalamus, central nucleus of the amygdala, or auditory cortex. Conclusion: CIE withdrawal produced multiple indices of negative affect in C57BL/6J females, suggesting that their motivation to consume alcohol may differ from air‐exposed counterparts despite equivalent intake. Contrasted with our previous findings in males, LBN‐induced mechanical hyperalgesia in chronic alcohol drinkers was specific to females. Lower nociceptive thresholds combined with increased sensitivity to the acute antinociceptive effect of ethanol may contribute to reinforcing ethanol consumption in LBN females but are not sufficient to increase their intake. Abstract : Adult C57BL/6J female mice exposed to early life adversity had lower mechanical pain thresholds upon withdrawal from chronic alcohol drinking and a higher sensitivity to the acute antinociceptive effect of alcohol. Combined with our earlier findings on alcohol intake, the present results suggest that the relief of hyperalgesia by alcohol is not sufficient to escalate voluntary alcohol consumption in female mice. Illustration created with BioRender.com .